Carbon nano horn and bovine serum albumin hierarchical composite: towards bio-friendly superhydrophobic protein film surfaces - Jadhav, Anil D.; Ogale, Satishchandra B.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2008)
Highly hydrophilic glass substrates when coated with films of carbon nano horns dispersed in the ubiquitous protein bovine serum albumin display hydrophobic characteristics. Incidentally both the materials used to create the final hydrophobic surface are known to be highly bio-compatible. The features observed are accredited to the replication of the micro and nanoscale hierarchical structures of carbon nano horns in the final film composite.